A silicon-carbon negative electrode material with double-layer protection structure and preparation method thereof

By adopting a silicon-carbon negative electrode material with a double-layer protective structure in lithium-ion batteries, using the combination of porous carbon and graphite, the problem of poor volume expansion and conductivity of silicon-based materials during circulation is solved, and efficient electrochemical performance is achieved and stability, suitable for high energy density lithium-ion batteries.

CN118507697BActive Publication Date: 2024-12-20GANZHOU RUIFUTE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410954350.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2024-12-20
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

During the circulation process, silicon-based lithium-ion batteries have rapid capacity decay due to volume expansion, powdering, poor electrical contact and unstable solid electrolyte interface masks, which makes them difficult to apply to high-energy-density lithium-ion batteries.

Method used

Silicon-carbon negative electrode material adopts a double-layer protective structure, dispersing nanosilicon in porous carbon and forming a conductive network with graphite as the substrate, and finally gas-phase coating is carried out to form a double-layer protective structure to suppress the volume expansion of silicon and on the outer surface. A uniform SEI film is formed.

Benefits of technology

It effectively suppresses the volume expansion of silicon, improves the conductivity, improves the first-effect and cycling stability, extends the capacity attenuation speed, and realizes a low-cost and high-performance silicon-carbon composite negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118507697B_ABST
    Figure CN118507697B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of negative electrode materials for lithium-ion batteries, and specifically relates to a silicon-carbon negative electrode material with a double-layer protective structure and a preparation method thereof. The preparation method includes dispersion of nano-silicon, mixing of nano-silicon with porous carbon and graphite, rotary evaporation, CVD gas phase coating, and screening. The present invention aims at a low-cost, high-performance silicon-carbon negative electrode, and synthesizes a double-layer protective structure silicon-carbon composite material negative electrode with excellent electrochemical properties through structural design, which can not only effectively inhibit the volume expansion of silicon, but also improve the conductive properties of the negative electrode material. At the same time, the outer protective layer can effectively block the electrolyte from entering the interior of the material, forming a uniform SEI film on the outer surface, thereby improving the initial effect and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery negative electrode materials, and specifically relates to a silicon-carbon negative electrode material with a double-layer protection structure and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are considered to be an efficient and convenient energy storage device. However, the graphite anode commonly used in commercial lithium-ion batteries has a low specific capacity, which makes it difficult to use it as a negative electrode material for high-energy-density lithium-ion batteries. Among the many known new negative electrode materials, silicon has high theoretical capacity, low operating voltage platform, rich resources, and environmental protection, and is considered to be a negative electrode material with great development potential.

[0003] However, unlike the lithiation mechanism of carbon materials, the volume of silicon anode changes greatly during the (de)lithiation process and needs to undergo multiple crystallographic phase transitions, which will shorten the cycle life of silicon-based lithium-ion batteries and cause battery failure. In addition, at room temperature, crystalline silicon undergoes a crystalline to amorphous phase transition during the first lithiation process and then remains in an amorphous state. At room temperature, the product of complete lithiation of silicon material is Li 15 Si4, so the theoretical capacity of silicon in a lithium-ion battery at room temperature is 3579 mAh / g.

[0004] From the above-mentioned properties of silicon negative electrode materials, it can be seen that silicon can combine with lithium metal to form Li even at room temperature. 15 Si4 alloy has high lithium storage capacity, but it is also accompanied by serious volume expansion, material pulverization and shedding, and rapid capacity decay. It can be summarized that silicon materials have four problems in the long-term cycle process: pulverization, poor electrical contact, unstable solid electrolyte interface film, and poor conductivity.

[0005] Therefore, the development of low-cost, high-performance silicon-based anode materials is of great significance for the practical application of high energy density lithium-ion batteries. Summary of the invention

[0006] In view of the above defects or improvement needs of the prior art, the present invention provides a silicon-carbon negative electrode material with a double-layer protective structure and a preparation method thereof. The silicon-carbon negative electrode material has a double protective layer and a multi-dimensional conductive network structure, which can effectively inhibit the volume expansion of silicon and improve the conductive properties of the negative electrode material. At the same time, the outer protective layer can effectively block the electrolyte from entering the interior of the material, forming a uniform SEI film on the outer surface to improve the initial effect.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The first object of the present invention is to provide a method for preparing a silicon-carbon negative electrode material with a double-layer protective structure, comprising the following steps:

[0009] S1. Add micron-sized silicon powder into a ball mill containing zirconium oxide beads, then add a dispersant and alternately ball mill at a speed of 300-800 r / min for 8-24 hours, then filter and wash to obtain a dispersed nano-silicon solution;

[0010] S2, ultrasonically dispersing the nano-silicon solution obtained in S1 for 15-30 minutes, then adding the porous carbon material, and continuing ultrasonically dispersing for 15-30 minutes to obtain a uniformly mixed solution;

[0011] S3, adding a surfactant to the mixed solution obtained in S2 for pretreatment, then adding a certain proportion of graphite for mixing, and ultrasonically dispersing for 0.5-2.0h to obtain a mixed slurry;

[0012] S4, placing the mixed slurry obtained in S3 into a rotary evaporator for rotary evaporation, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and then continuing rotary evaporation to obtain a mixed powder of nano-silicon, porous carbon and graphite;

[0013] S5, putting the nano silicon graphite mixed powder obtained in S4 into a reactor, evacuating the reactor and starting the rotary button, then introducing N2, raising the temperature to 500-820°C twice and keeping the temperature, then introducing acetylene or methane gas for CVD gas phase coating, stopping the introduction of gas after the coating is completed, continuing to raise the temperature to 850-950°C and keeping the temperature for 2h, and cooling to obtain Si / G / C powder material (silicon / graphite / carbon powder material);

[0014] S6. The Si / G / C powder material obtained in S5 is sieved with a 325-mesh molecular sieve to obtain a silicon-carbon negative electrode material.

[0015] The volume expansion of Si is about 300%, while that of graphite is only about 20%. The preparation principle of the present invention is: before CVD vapor coating of Si, nano-silicon is allowed to enter the pores of porous carbon to suppress the volume effect of silicon; then secondary mixing is performed with graphite as the substrate to form a conductive network to improve its conductivity; finally, vapor coating is performed to form a double-layer protective structure. During charging and discharging, micron-sized graphite (D 50 =16um) and nano-scale Si expand, and the space for the expansion of micron-scale graphite provides enough space for the expansion of nano-silicon, which can limit its expansion and inhibit its volume change; the outermost coating layer has the function of improving the initial effect and improving stability.

[0016] Furthermore, in the above technical solution S1, the diameter of the zirconia beads is 0.3-1.0 mm, and the ball-to-material ratio is 1-3:1; the dispersant is polyvinyl alcohol or dodecyl polyethoxyethylene ether, and the added amount is 5-15% of the total mass of the micron-grade silicon powder, preferably 5%.

[0017] Furthermore, in the above technical solution S1, the D50 of the nano-silicon solution is 60 nm.

[0018] Furthermore, in the above technical solution S2, the pore size of the porous carbon material is 0.5-2 μm.

[0019] Furthermore, in the above technical solution S3, the surfactant is tetrabutylammonium fluoride; the pretreatment method is: adding a surfactant to the mixed solution, stirring at a speed of 500-1500r / min until the free nano-silicon and the silicon dispersed on the surface of the porous carbon material are positively charged.

[0020] Furthermore, the mass ratio of nano-silicon, porous carbon material and graphite described in the above technical solution is 5:10-20:75-85.

[0021] Furthermore, in the above technical solution S4, the conditions for rotary evaporation are: temperature 60-80°C, rotation speed 20-60r / min.

[0022] Furthermore, in the above technical solution S5, the flow rate of N2 is 2-8 L / min, and the heating method is: heating to 500°C at 5°C / min, keeping warm for 1-2h, and then continuing to heat to 820°C at 5°C / min.

[0023] Furthermore, in the above technical solution S5, the flow rate of acetylene or methane gas is 0.5-5 L / min, the coating time is 4-12 h; the temperature is increased to 850-950° C. at 5° C. / min; and the rotation speed of the reactor is 15 Hz.

[0024] The second object of the present invention is to provide a silicon-carbon negative electrode material with a double-layer protective structure, which is prepared by the above-mentioned preparation method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention aims at preparing a low-cost, high-performance silicon-carbon negative electrode, and synthesizes a silicon-carbon composite material negative electrode with excellent electrochemical performance through structural design; by using micron-level silicon powder as a raw material, after simple ball milling into nanometer level, and dispersing and mixing with porous carbon as a substrate, a precursor material with nano-silicon uniformly dispersed in the pores and on the surface is obtained; then, the precursor material is mixed with graphite for a second time, a small amount of silicon that is not well dispersed and scattered outside the porous carbon pores is adsorbed, and a multi-dimensional conductive network is constructed at the same time; finally, the nano-silicon-graphite mixed powder is CVD vapor-coated, so that the surface of the material is covered with a coating layer of about 20nm, and the porous carbon is closed at the same time, and a silicon-carbon composite material with a double protective layer and a multi-dimensional conductive network structure is successfully prepared, which can not only effectively inhibit the volume expansion of silicon, but also improve the conductive performance of the negative electrode material, and at the same time, the outer protective layer can effectively block the electrolyte from entering the interior of the material, forming a uniform SEI film on the outer surface, thereby improving the first effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a scanning electron microscope image of the mixed powder material obtained by S4 in Example 1 of the present invention.

[0029] Figure 2 This is a scanning electron microscope image of the Si / G / C powder material obtained by S5 in Example 1 of the present invention.

[0030] Figure 3 This is the first cycle charge and discharge curve of the silicon-carbon negative electrode material obtained in the present invention.

[0031] Figure 4 It is a cyclic stability analysis diagram of Examples 1-3 of the present invention and Comparative Examples 1-3.

[0032] Figure 5 This is a transmission electron microscope image of the Si / G / C powder material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials involved in the following examples are common commercial products and can be purchased from the market unless otherwise specified.

[0034] The above-mentioned technical features of the present invention and the technical features specifically described below (such as implementation cases) can be combined with each other to form a new or preferred technical solution.

[0035] The raw materials involved in the embodiments of the present invention are either existing commercially available products or can be prepared according to existing methods.

[0036] Example 1

[0037] A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure comprises the following steps:

[0038] S1. Add micron-sized silicon powder (D50=20μm) into a ball mill, then add polypropylene alcohol and 0.3mm diameter zirconium oxide beads, with a ball-to-material ratio of 2:1 and a polypropylene alcohol content of 5%; alternately ball mill at a speed of 500r / min for 16h, and then filter and wash to obtain a nano-silicon solution with a D50 of 60nm;

[0039] S2, subjecting the nano-silicon solution obtained in S1 to ultrasonic treatment for 15 minutes, and then adding a porous carbon material with a pore size of about 1 μm, wherein the mass ratio of the porous carbon to the nano-silicon is 3:1, and continuing ultrasonic treatment for 30 minutes to obtain a uniformly mixed solution;

[0040] S3, adding the mixed solution obtained in S2 to a tetrabutylammonium fluoride solution for pretreatment, and then adding graphite for dispersion and mixing, the mixed solution and the graphite have opposite charges; the mass ratio of nano-silicon, porous carbon, and graphite is 5:15:80; then stirring and ultrasonically dispersing for 2 hours to obtain a mixed slurry;

[0041] S4, placing the mixed slurry obtained in S3 into a rotary evaporator, performing rotary evaporation at 65°C and 25 r / min, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and continuing rotary evaporation to obtain a mixed powder of nano-silicon, porous carbon and graphite;

[0042] S5, putting the nano-silicon graphite mixed powder obtained in S4 into a reactor, evacuating the reactor, then introducing N2 at 8L / min, heating to 500°C at 5°C / min, and keeping warm for 1h; then continuing to heat to 820°C at 5°C / min, introducing acetylene gas at 2L / min for CVD gas phase coating, the coating time is 4h, after the coating is completed, stop introducing acetylene gas, and heat to 920°C at 5°C / min and keep warm for 2h. The reactor speed during the whole process is 15H Z , then cooled to obtain Si / G / C powder material;

[0043] S6. The Si / G / C powder material obtained in S5 is sieved with a 325-mesh molecular sieve to obtain a product silicon-carbon negative electrode material.

[0044] Example 2

[0045] A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure comprises the following steps:

[0046] S1. Add micron-sized silicon powder (D50=20μm) into a ball mill, then add polypropylene alcohol and 0.3mm diameter zirconium oxide beads, with a ball-to-material ratio of 2:1 and a polypropylene alcohol content of 5%; alternately ball mill at a speed of 500r / min for 16h, and then filter and wash to obtain a nano-silicon solution with a D50 of 60nm;

[0047] S2, subjecting the nano-silicon solution obtained in S1 to ultrasonic treatment for 15 minutes, and then adding a porous carbon material with a pore size of about 1 μm, wherein the mass ratio of the porous carbon to the nano-silicon is 4:1, and continuing ultrasonic treatment for 30 minutes to obtain a uniformly mixed solution;

[0048] S3, adding the mixed solution obtained in S2 to a tetrabutylammonium fluoride solution for pretreatment, and then adding graphite for dispersion and mixing, the mixed solution and the graphite have opposite charges; the mass ratio of nano-silicon, porous carbon, and graphite is 5:20:75; then stirring and ultrasonically dispersing for 2 hours to obtain a mixed slurry;

[0049] S4, placing the mixed slurry obtained in S3 into a rotary evaporator, performing rotary evaporation at 65°C and 25 r / min, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and continuing rotary evaporation to obtain a mixed powder of nano-silicon, porous carbon and graphite;

[0050] S5, putting the nano-silicon graphite mixed powder obtained in S4 into a reactor, evacuating the reactor, then introducing N2 at 8L / min, heating to 500°C at 5°C / min, and keeping warm for 1h; then continuing to heat to 820°C at 5°C / min, introducing acetylene gas at 2L / min for CVD gas phase coating, the coating time is 4h, after the coating is completed, stop introducing acetylene gas, and heat to 950°C at 5°C / min and keep warm for 2h. The reactor speed during the whole process is 15H Z , then cooled to obtain Si / G / C powder material;

[0051] S6. The Si / G / C powder material obtained in S5 is sieved with a 325-mesh molecular sieve to obtain a product silicon-carbon negative electrode material.

[0052] Example 3

[0053] A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure comprises the following steps:

[0054] S1. Add micron-sized silicon powder (D50=20μm) into a ball mill, then add polypropylene alcohol and 0.3mm diameter zirconium oxide beads, with a ball-to-material ratio of 2:1 and a polypropylene alcohol content of 5%; alternately ball mill at a speed of 500r / min for 16h, and then filter and wash to obtain a nano-silicon solution with a D50 of 60nm;

[0055] S2, subjecting the nano-silicon solution obtained in S1 to ultrasonic treatment for 15 minutes, and then adding a porous carbon material with a pore size of about 1 μm, wherein the mass ratio of the porous carbon to the nano-silicon is 2:1, and continuing ultrasonic treatment for 30 minutes to obtain a uniformly mixed solution;

[0056] S3, adding the mixed solution obtained in S2 to a tetrabutylammonium fluoride solution for pretreatment, and then adding graphite for dispersion and mixing, the mixed solution and the graphite have opposite charges; the mass ratio of nano-silicon, porous carbon, and graphite is 5:10:85; then stirring and ultrasonically dispersing for 2 hours to obtain a mixed slurry;

[0057] S4, placing the mixed slurry obtained in S3 into a rotary evaporator, performing rotary evaporation at 65°C and 25 r / min, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and continuing rotary evaporation to obtain a mixed powder of nano-silicon, porous carbon and graphite;

[0058] S5, putting the nano-silicon graphite mixed powder obtained in S4 into a reactor, evacuating the reactor, then introducing N2 at 8L / min, heating to 500°C at 5°C / min, and keeping warm for 1h; then continuing to heat to 820°C at 5°C / min, introducing acetylene gas at 2L / min for CVD gas phase coating, the coating time is 4h, after the coating is completed, stop introducing acetylene gas, and heat to 850°C at 5°C / min and keep warm for 2h. The reactor speed is 15H during the whole process. Z , then cooled to obtain Si / G / C powder material;

[0059] S6. The Si / G / C powder material obtained in S5 is sieved with a 325-mesh molecular sieve to obtain a product silicon-carbon negative electrode material.

[0060] Comparative Example 1

[0061] A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure comprises the following steps:

[0062] S1. Add micron-sized silicon powder (D50=20μm) into a ball mill, then add polypropylene alcohol and 0.3mm diameter zirconium oxide beads, with a ball-to-material ratio of 2:1 and a polypropylene alcohol content of 5%; alternately ball mill at a speed of 500r / min for 16h, and then filter and wash to obtain a nano-silicon solution with a D50 of 60nm;

[0063] S2, adding the nano silicon solution obtained in S1 to a tetrabutylammonium fluoride solution for pretreatment, and then adding graphite for dispersion and mixing, the mixed solution and the graphite have opposite charges; the mass ratio of nano silicon to graphite is 5:95; then stirring and ultrasonically dispersing for 2 hours to obtain a mixed slurry;

[0064] S3, placing the mixed slurry obtained in S2 into a rotary evaporator, performing rotary evaporation at 65°C and 25 r / min, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and continuing rotary evaporation to obtain nano-silicon graphite mixed powder;

[0065] S4, putting the nano-silicon-graphite mixed powder obtained in S3 into a reactor, evacuating the reactor, then introducing N2 at 8 L / min, heating to 500°C at 5°C / min, and keeping warm for 1 hour; then continuing to heat to 820°C at 5°C / min, introducing acetylene gas at 2 L / min for CVD gas phase coating, the coating time is 4 hours, after the coating is completed, stop introducing acetylene gas, and heat to 920°C at 5°C / min and keep warm for 2 hours. The reactor speed during the whole process is 15H Z , then cooled to obtain Si / G powder material;

[0066] S5. The Si / G powder material obtained in S4 is sieved with a 325-mesh molecular sieve to obtain a product silicon-carbon negative electrode material.

[0067] Comparative Example 2

[0068] A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure comprises the following steps:

[0069] S1. Add micron-sized silicon powder (D50=20μm) into a ball mill, then add polypropylene alcohol and 0.3mm diameter zirconium oxide beads, with a ball-to-material ratio of 2:1 and a polypropylene alcohol content of 5%; alternately ball mill at a speed of 500r / min for 16h, and then filter and wash to obtain a nano-silicon solution with a D50 of 60nm;

[0070] S2, subjecting the nano-silicon solution obtained in S1 to ultrasonic treatment for 15 minutes, and then adding a porous carbon material with a pore size of about 1 μm, wherein the mass ratio of the porous carbon to the nano-silicon is 95:5, and continuing ultrasonic treatment for 30 minutes to obtain a uniformly mixed solution;

[0071] S3, placing the mixed solution obtained in S2 into a rotary evaporator, and performing rotary evaporation at 65°C and 25 r / min, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and then continuing rotary evaporation to obtain nano-silicon porous carbon mixed powder;

[0072] S4, put the nano-silicon porous carbon mixed powder obtained in S3 into a reactor, evacuate the reactor, then introduce N2 at 8L / min, heat to 500℃ at 5℃ / min, and keep warm for 1h; then continue to heat to 820℃ at 5℃ / min, introduce acetylene gas at 2L / min for CVD gas phase coating, the coating time is 4h, stop introducing acetylene gas after coating, heat to 920℃ at 5℃ / min and keep warm for 2h, the reactor speed is 15H during the whole process Z , then cooled to obtain Si / C powder material;

[0073] S5. The Si / C powder material obtained in S4 is sieved with a 325-mesh molecular sieve to obtain a product silicon-carbon negative electrode material.

[0074] Comparative Example 3

[0075] A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure comprises the following steps:

[0076] S1. Add micron-sized silicon powder (D50=20μm) into a ball mill, then add polypropylene alcohol and 0.3mm diameter zirconium oxide beads, with a ball-to-material ratio of 2:1 and a polypropylene alcohol content of 5%; alternately ball mill at a speed of 500r / min for 16h, and then filter and wash to obtain a nano-silicon solution with a D50 of 60nm;

[0077] S2, subjecting the nano-silicon solution obtained in S1 to ultrasonic treatment for 15 minutes, and then adding a porous carbon material with a pore size of about 1 μm, wherein the mass ratio of the porous carbon to the nano-silicon is 2:1, and continuing ultrasonic treatment for 30 minutes to obtain a uniformly mixed solution;

[0078] S3, adding the mixed solution obtained in S2 to a tetrabutylammonium fluoride solution for pretreatment, and then adding graphite for dispersion and mixing, the mixed solution and the graphite have opposite charges; the mass ratio of nano-silicon, porous carbon, and graphite is 5:10:85; then stirring and ultrasonically dispersing for 2 hours to obtain a mixed slurry;

[0079] S4, placing the mixed slurry obtained in S3 into a rotary evaporator, performing rotary evaporation at 65°C and 25 r / min, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and continuing rotary evaporation to obtain a mixed powder of nano-silicon, porous carbon and graphite;

[0080] S5. The mixed powder of nano-silicon, porous carbon and graphite obtained in S4 is sieved with a 325-mesh molecular sieve to obtain a silicon-carbon negative electrode material.

[0081] Test example

[0082] In order to detect the performance of the silicon-carbon negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 for lithium-ion batteries, tests were performed using a half-cell test method, a 18650 steel shell full battery, a scanning electron microscope, and a specific surface area and porosity analyzer.

[0083] The half-cell test method is to use the prepared silicon-carbon negative electrode material as the negative electrode active material to make a slurry, and the slurry ratio is: active material: CNTs (including dispersant): CMC: SBR = 89%: 4.5%: 1.5%: 5%. The slurry is then coated on copper foil and vacuum dried for 12 hours to make a negative electrode sheet. The electrolyte is purchased commercially, the separator is a PE film, and the lithium sheet is the counter electrode. It is assembled into a half-cell in a glove box. Constant current charge and discharge experiments are carried out in the LAND battery test system. The charge and discharge voltage is limited to 0.005-2V, and a computer-controlled charge and discharge cabinet is used for data collection and control. The results are shown in Table 1 and Figure 1-5 shown.

[0084] Table 1 Power-off test results

[0085]

[0086] From Table 1 and Figure 4 It can be seen that from the comprehensive perspective of first effect, electrode expansion and cycle stability, the buckling test result of Example 1 is the best, and the capacity of Comparative Example 3 is relatively high. This may be because Comparative Example 3 did not undergo CVD gas phase coating, resulting in a higher silicon content and a higher capacity; but the first effect of Comparative Example 3 is significantly lower than that of other embodiments. This is because Comparative Example 3 did not undergo CVD gas phase coating, resulting in an uneven SEI film formed therein and the electrolyte was able to enter the pores of the material, increasing side reactions, resulting in a low first efficiency.

[0087] From Examples 2 and 3 and Comparative Examples 1 and 2, the cyclic stability of nano-silicon compounded with porous carbon or graphite alone is poorer than that of the silicon-carbon material compounded together. This is because the single compound fails to disperse the nano-silicon into an ideal state, and there is some free silicon, resulting in poor cyclic stability.

[0088] The above embodiments show that the method of the present invention is used to evenly disperse nano-silicon and porous carbon in the pores, and then graphite is used to adsorb silicon that is not well dispersed and is discrete outside the porous carbon pores, and finally gas-phase coating is performed. The prepared silicon-carbon negative electrode material can not only effectively inhibit the volume expansion of silicon, but also the outer protective layer can effectively block the electrolyte from entering the interior of the material, forming a uniform SEI film on the outer surface, thereby improving the first effect, prolonging the capacity decay rate, and having excellent overall performance.

[0089] In addition, from Figure 1 It can be seen that after two dispersions, nano-silicon has been evenly dispersed on the graphite surface, and the dispersion effect is good; Figure 2 and Figure 5 In the experiment, after gas phase coating, the nano silicon particles on the graphite surface have been evenly coated, and the coating effect is good; Figure 3 This is the first cycle charge and discharge curve of the obtained silicon-carbon negative electrode material. It can be seen that the reversible specific capacity is 455mAh / g and the first coulombic efficiency is 95%.

[0090] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material with a double-layer protective structure, characterized in that: The steps include: S1. Add micron-sized silicon powder into a ball mill containing zirconium oxide beads, then add a dispersant and alternately ball mill at a speed of 300-800 r / min for 8-24 hours, then filter and wash to obtain a dispersed nano-silicon solution; S2, ultrasonically dispersing the nano-silicon solution obtained in S1 for 15-30 minutes, then adding the porous carbon material, and continuing ultrasonically dispersing for 15-30 minutes to obtain a uniformly mixed solution; S3, adding a surfactant to the mixed solution obtained in S2 for pretreatment, then adding a certain proportion of graphite for mixing, and ultrasonically dispersing for 0.5-2.0h to obtain a mixed slurry; the surfactant is tetrabutylammonium fluoride; the pretreatment method is: adding a surfactant to the mixed solution, stirring at a speed of 500-1500r / min until the free nano-silicon and the silicon dispersed on the surface of the porous carbon material are positively charged; The mass ratio of the nano-silicon, porous carbon material and graphite is 5:10-20:75-85; S4, placing the mixed slurry obtained in S3 into a rotary evaporator for rotary evaporation, filtering and washing the powder obtained by rotary evaporation with deionized water for 2-3 times, and then continuing rotary evaporation to obtain a mixed powder of nano-silicon, porous carbon and graphite; S5, putting the mixed powder obtained in S4 into a reactor, evacuating the reactor and starting the rotary button, then introducing N2, heating to 500-820°C twice, and keeping the temperature, then introducing acetylene or methane gas for CVD gas phase coating, so that the surface of the material is covered with a 20nm coating layer, and the porous carbon is closed at the same time, and the gas is stopped after the coating is completed, and the temperature is continued to be raised to 850-950°C and kept for 2h, and then cooled to obtain Si / G / C powder material; wherein, the flow rate of N2 introduced is 2-8L / min, and the heating method is: heating to 500°C at 5°C / min, keeping the temperature for 1-2h, and then continuing to heat to 820°C at 5°C / min; the flow rate of acetylene or methane gas introduced is 0.5-5L / min, and the coating time is 4-12h; S6. The Si / G / C powder material obtained in S5 is sieved with a 325-mesh molecular sieve to obtain a silicon-carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In S1, the diameter of the zirconia beads is 0.3-1.0 mm, and the ball-to-material ratio is 1-3:1; the dispersant is polyvinyl alcohol or dodecyl polyethoxyethylene ether, and the added amount is 5-15% of the total mass of the micron-grade silicon powder.

3. The preparation method according to claim 1, characterized in that: In S1, the nano-silicon solution has a D 50 It is 60nm.

4. The preparation method according to claim 1, characterized in that: In S2, the pore size of the porous carbon material is 0.5-2 μm.

5. The preparation method according to claim 1, characterized in that: In S4, the conditions for rotary evaporation are: temperature 60-80°C, rotation speed 20-60r / min.

6. The preparation method according to claim 1, characterized in that: In S5, the temperature is raised to 850-950°C at a rate of 5°C / min; the rotation speed of the reactor is 15 Hz.

7. A silicon-carbon negative electrode material with a double-layer protective structure, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.